The Impact of Accounting Digitalization on Financial Efficiency at PT Bukit Asam Tbk - Nur Fadia Fadilah; Sumarni; Muh Rifki Suaib; Muchriana Muchran (www.amertainstitute.com, 2025)
This research aims to analyze the influence of accounting digitalization on financial efficiency at PT Bukit Asam Tbk. Using a descriptive quantitative and associative approach, the data analyzed consists of quarterly operating profit reports from 2019–2024, before and after the implementation of digital systems such as ERP, e-Invoice, and the CISEA application. The analysis technique used is the Wilcoxon Signed-Rank Test, as the data is not normally distributed. The results show that there is a significant difference between profits before and after digitalization, with a significance value right at the threshold (p = 0.05). This indicates that accounting digitalization contributes positively to the improvement of the company's financial efficiency, although its impact needs to be studied further in the long term. Factors supporting the effectiveness of digitalization include technology infrastructure, management commitment, and human resources readiness; while its obstacles consist of internal resistance and a lack of system evaluation. This study provides empirical contributions in the context of digital transformation of mining companies in Indonesia and enriches the literature on efficiency based on accounting information systems.